2018
DOI: 10.1002/jum.14728
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Ultrasound‐Guided and Landmark‐Based Lumbar Punctures in Inexperienced Resident Physicians

Abstract: The use of US guidance to assist in lumbar punctures did not improve the procedural success rate over traditional landmark techniques in an academic setting with novice providers. Although using US for procedural guidance significantly decreased the number of attempts, it seemed to have no effect on postprocedural pain or the time to obtain CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…Similarly, the number of insertion attempts was reduced with the US use as well as the number of needle redirection. One the other hand, a prospective study that examined the use of US in LP by emergency medicine residents did not find a statistically significant difference in the success rate between the two groups, although a statistically significant difference in the number of attempts was shown in favor of the US group [6].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, the number of insertion attempts was reduced with the US use as well as the number of needle redirection. One the other hand, a prospective study that examined the use of US in LP by emergency medicine residents did not find a statistically significant difference in the success rate between the two groups, although a statistically significant difference in the number of attempts was shown in favor of the US group [6].…”
Section: Discussionmentioning
confidence: 84%
“…This can be difficult in certain patients (e.g., obese or pregnant patients). Ultrasound (US) can be a safe, non-invasive, easy to learn, and cost-effective tool that can assist in identifying the anatomic landmarks [4][5][6][7][8]. The first use of US for this purpose was described by Russian anesthesiologists in 1971 [9].…”
Section: Introductionmentioning
confidence: 99%
“…At least 12 randomized controlled studies have been published comparing the use of ultrasound guidance vs landmarks for the performance of LP or spinal anesthesia in adult patients, which were not included in the abovementioned meta‐analyses. These individual studies demonstrated similar benefits of using ultrasound guidance: reduced needle insertion attempts, reduced needle redirections, and increased overall procedural success rates 17,31,37,40,41,43‐49 …”
Section: Recommendationsmentioning
confidence: 89%
“…Therefore, data from these three ultrasound‐guided procedures are often pooled. Currently, at least 33 randomized controlled studies comparing ultrasound‐guided vs landmark‐guided site selection for LP, epidural catheterization, or spinal anesthesia have been published 22‐49 . We present three meta‐analyses below that pooled data primarily from randomized controlled studies comparing ultrasound‐guided vs landmark‐guided site selection for LP or spinal anesthesia.…”
Section: Recommendationsmentioning
confidence: 99%
“…Another study by Evans et al showed that the use of US guidance to assist in lumbar punctures did not improve the procedural success rate over traditional landmark techniques in an academic setting with novice providers [16]. The reason for the heterogeneity of results could be due to the facts that in many studies the full spectrum of trainees, from junior residents to fellows, is assessed, and because the US scanning is variably done either by the trainees themselves or by the principal investigator depending on the study.…”
Section: Discussionmentioning
confidence: 99%